Failure of NIV in acute asthma: case report and a word of caution. Issue 2 (26th January 2006) - Agarwal, R; Malhotra, P; Gupta, D
Abstract : Noninvasive ventilation (NIV) is the provision of ventilatory support without the need for an invasive airway, and has revolutionized the management of patients with diverse forms of respiratory failure. The advantages of NIV include improved patient comfort and reduced need for sedation, while avoiding the complications of endotracheal intubation, including upper airway trauma, sinusitis, otitis, and nosocomial pneumonia. In selected patients, NIV has also been shown to improve survival. The role of NIV in acute severe asthma is at best controversial. In this case report, we describe a patient with acute severe asthma who was initially managed and failed with NIV, and was successfully managed with invasive ventilation. We also review the pathophysiological mechanisms of benefit of NIV in acute severe asthma, and the current literature on the use of NIV in acute asthma. In conclusion, a trial of NIV in acute asthma may be justified in carefully selected and monitored patients who do not respond to initial medical therapy. However, as its role is not clear and as the condition of an asthmatic patient may deteriorate abruptly, extreme caution is advisable to recognize failure of NIV as in the case presented here. Facilities for immediate endotracheal intubation and next level of treatment should be readily available.